Child Support in the United States: An Uncertain and Irregular Income Source? - Cancian, Maria; Meyer, Daniel R. (My University, 2005)
While most mothers with child-support orders receive support, the amount they receive varies substantially, the researchers find upon examining the situations of 14,729 Wisconsin mothers with new child support orders in 2000. Drawing on data from 2001-2003, this study finds that variation in child-support income varies year to year and within a year. More than one-third of families experienced declines or increases of $1,000 or more in support  from one year to the next.